DIMENSI SOSIAL PADA SISI KEBUTUHAN (DEMAND SIDE) BAGI PERAWATAN IBU DAN ANAK - Ni Komang Yuni Rahyani (Jurnal Skala Husada : The Journal of Health, 2017)
Abstract : Midwifery care must be given in accordance with the needs of mothers as users of health services , and the demand side are based on a variety of factors , namely the availability of quality service and comprehensive and competent personnel. The purpose of writing this article is to give an overview of the factors as a social determinant of fulfillment of health services for mothers and newborns from demand side . The availability of , access to and improvement of maternity services was a major problem , especially in developing countries and in poor countries . Determinants of demand-side as factors that affect the needs at the level of individuals, households and communities . Care or midwifery care in accordance with the standards , especially meet maternal health care coverage as a key priority at this time must meet availability , affordability and effectiveness of services .Keywords: demand-side, midwifery care, accessibility, effectiveness